Genoeg is genoeg Over gezondheidszorg en democratie - Trappenburg, Margo (Studies over politieke vernieuwing, 2008)
Since some years there has been a significant trend in the democratization of health care in the Netherlands. Where in the old days patients used to be able to just rest and receive care, nowadays they have to get active. Not only do they have to keep working as much as possible, they are expected to actively participate in their own treatment, like finding out where you can get the best doctor or how to give yourself injections. Also they have to participate in client councils of the hospital. In this book, Margo Trappenburg discusses the positive but foremost the negative aspects of this hyper- democratization of health care.